Implementing Edupreneurship in Developing Islamic Religious Education Learning at SDN Pager 1 Purwosari - Muhammad Zainul Arifin; Ahmad Ma’ruf; Ali Mohtarom; M Jamhuri (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to identify the form or concept of edupreneurship as well as its implementation in developing Islamic Religious Education (PAI) at SDN Pager 1 Purwosari. Edupreneurship is a learning approach that combines entrepreneurial values with the educational process to shape students’ character to be independent, honest, creative, disciplined, and responsible in accordance with Islamic values. This study employs a qualitative method with a descriptive research design. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects included PAI teachers and students at SDN Pager 1 Purwosari. The results of the study indicate that the edupreneur approach in PAI instruction is implemented through active learning activities, group work, discussions, and handson practices related to students’ daily lives. The implementation of edupreneurship was applied to the topics of almsgiving, voluntary charity, and zakat through simple practical activities such as collecting alms, sharing activities, simulating zakat calculations, and distributing aid to those in need. Through these activities, students not only understand religious concepts theoretically but also are able to apply these teachings in their daily lives. The application of edupreneurship in PAI instruction has a positive impact on the development of students’ character, such as increased independence, honesty, discipline, responsibility, cooperation, and social awareness.Thus, the implementation of the edupreneur model can help make Islamic Education (PAI) lessons more active, engaging, and meaningful for students at SDN Pager 1 Purwosari.